The Effectiveness of Using Pianika Media to Introduce the Song 'Ibu Kita Kartini' in Pancasila Education - Elrika, Anastasia Jevis; Febriyanti, Dian Kavita; Wijayanto, Wasis (Jurnal Prajaiswara, 2025)
Introduction/Main Objectives: This study aims to determine the effectiveness of using pianika media in learning the national song “Ibu Kita Kartini” to instill Pancasila values in elementary school students. Research Methods: The researcher used a narrative qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research subjects were 13 grade II students and one teacher at Kayuapu Elementary School. Data analysis was conducted using the Miles & Huberman model with validation through source and technique triangulation. Finding/Results: The results showed that the use of pianika in learning national songs was able to increase students' enthusiasm, active involvement, and understanding of the meaning of songs and Pancasila values. Students look more active, happy, and show a sense of pride when playing songs using the pianika. Conclusion This study shows that pianika media is effective in learning national songs because it is able to combine cognitive, affective, and psychomotor aspects. In addition, this media is also able to strengthen the cultivation of character and nationalism values through a fun and meaningful learning experience.